2006
DOI: 10.1098/rspb.2006.3660
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens, density dependence and the coexistence of tropical trees

Abstract: There is increasing interest in the role played by density-dependent mortality from natural enemies, particularly plant pathogens, in promoting the coexistence and diversity of tropical trees. Here, we review four issues in the analysis of pathogen-induced density dependence that have been overlooked or inadequately addressed. First, the methodology for detecting density dependence must be robust to potential biases. Observational studies, in particular, require a careful analysis to avoid biases generated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(163 citation statements)
references
References 60 publications
5
157
1
Order By: Relevance
“…Many studies of density dependence neglect to differentiate between effects of intra-and inter-specific densities, a key component in assessing the role of density dependence in promoting species coexistence (Freckleton and Lewis 2006). We found a clear difference between conspecific and heterospecific neighbor effects at the community level, and for approximately one-half of the focal species examined.…”
Section: Effect Of Heterospecific Neighbors On Survivalmentioning
confidence: 70%
See 1 more Smart Citation
“…Many studies of density dependence neglect to differentiate between effects of intra-and inter-specific densities, a key component in assessing the role of density dependence in promoting species coexistence (Freckleton and Lewis 2006). We found a clear difference between conspecific and heterospecific neighbor effects at the community level, and for approximately one-half of the focal species examined.…”
Section: Effect Of Heterospecific Neighbors On Survivalmentioning
confidence: 70%
“…A CCT would also fail to arise if species always experienced high local densities of conspecifics, regardless of their abundance in the community, due to limited seed dispersal (Freckleton and Lewis 2006). Additionally, predator satiation at larger spatial scales could result in a positive relationship between seedling survival and species abundance, even in the face of local-scale negative density dependence (Schupp 1992).…”
Section: Community-level Consequences Of Local Density Dependencementioning
confidence: 99%
“…Along with fungi and insects, the Oomycota have long been thought to be one of the drivers of the JanzenConnell model. However, the degree of host-specificity is unknown for most Oomycota species 46 , and a fungicide study in Belize documented a non-significant effect by these protists 6 . If the Oomycota broadly drive the Janzen-Connell model, then we can expect their diversity to be very high, mirroring tree diversity.…”
Section: Discussionmentioning
confidence: 99%
“…It is of particular interest whether disease spread and the effect of a pathogen on plant fitness are dependent on the density of the host population. If effects of pathogens increase with plant density, pathogens have the potential to regulate host population size and alter spatial distributions (4,51). Several studies have demonstrated important density-dependent effects of disease in natural plant populations (18,21,55,75).…”
Section: Population Ecology and Geneticsmentioning
confidence: 99%
“…First, there is a need to dissect the black box of the soil community to understand which organisms and combinations contribute to ecologically relevant effects (106). Second, more detailed studies of patterns of plant density dependence, host specificity of pathogens, and the entire plant life cycle are needed to fully explore these hypotheses (51).…”
Section: Community and Ecosystem Ecologymentioning
confidence: 99%